Meningkatkan Kemampuan Siswa Materi Yesus Mewartakan Kerajaan Allah Melalui Mukjizat dengan Model PjBL Fase D Kelas 8 Jakarta Nanyang School, Tangerang - Maksimus Adil; Nerita Setianingtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in enhancing the ability of eighth-grade junior high school students to apply Jesus’ teachings about the proclamation of the Kingdom of God through daily actions and miracles. Catholic Religious Education (CRE) should not only emphasize cognitive knowledge but also encourage students to embody these values in their attitudes and behavior. The PjBL model facilitates this by providing opportunities for students to internalize their learning through real-life projects that, although simple, can be impactful and inspiring.The research was conducted in the first semester of the 2024–2025 academic year through two learning cycles. Each cycle consisted of one meeting for two teaching hours, followed by a third meeting for project presentations. Results showed that the PjBL model significantly improved students’ understanding of the Kingdom of God and motivated them to become agents of love in their daily lives.In the first cycle, students showed hesitation in implementing their projects, as observed by the teacher and reflected in their initial outcomes. However, after receiving positive feedback from the project recipients, students became more confident and enthusiastic. This was evident in the improved results of the second cycle, as well as in the students’ responses in surveys and project reports. Students acknowledged that the project helped them connect Jesus’ teachings with real-life situations and inspired them to continue evangelizing through action in everyday life.